Security as Part of the System of Value-Semantic Orientations of Russian National Guard Officers: A Case Study of Cadets - Officer Candidates - Mikhail S. Ivanov; Aleksey A. Utyuganov; Mikhail S. Yanitskiy; Andrey V. Seryi (Peoples' Friendship University of Russia (RUDN University), 2020)
The officers profession is of particular interest to psychology due to its deontological load and the complexity of moral and ethical foundations, when the humanistic orientation towards the protection of people and society presupposes a readiness to use the necessary violence. The study attempts to reveal this dialectic by analysing the content of the personal value-semantic sphere considered by Russian National Guard officers in terms of their professional orientation towards ensuring security. Methodologically, the study is based on the provisions of the value-semantic theory and the emerging theory of the psychology of personal security, according to which security is understood as a special value-semantic dimension that determines the subjects attitude to danger. The purpose of the study is to identify the professional value-semantic orientations of the officers and analyse them in terms of their focus on ensuring security, in the dynamics of their formation in the process of professional training, using the example of officer candidates (cadets) of the Russian National Guard troops, whose activities have clear axiological grounds. The research base comprised all existing military institutes of the Russian National Guard troops. The subjects were cadets ( N = 779). The research methods were non-formalised written surveys, verbalised self-reports on experimental tasks, content analysis, experiment, qualitative analysis, theoretical analysis and methods of mathematical statistics. Based on the results of the study, we could identify the core values of an officer (patriotism, military duty, security of the state and society, responsibility for subordinates, military partnership and tolerance) and describe the motives for choosing a military career and professional ideas about the ideal officer (the prevailing image of a defender, a professional who is able to effectively ensure the safety and defence of the Fatherland). It was found that the value orientations of the officers as well as the sense-making motives for their choosing military careers are closely related to the focus of professional activity on ensuring security. The study showed that, under a purposeful psychological and pedagogical influence, the cadets internally accepted all the highlighted professionally important values. In this case, the value of security was the most sensitive to the influence. In the conclusions, it is noted that the value of security of the state and society is one of the elements of the system of value-semantic orientations of the officers personality, and it is assumed that, since other professional values of the officer are related to security in semantic unity, the professional focus on ensuring security is one of the system-forming foundations of the value-semantic orientations of the officers personality.